Technological challenges and milestones for writing genomes. - Ostrov,N; Beal,J; Ellis,T; Gordon,DB; Karas,BJ; Lee,HH; Lenaghan,SC; Schloss,JA; Stracquadanio,G; Trefzer,A; Bader,JS; Church,GM; et al. (Science, 2019)
Engineering biology with recombinant DNA, broadly called synthetic biology, has progressed tremendously in the last decade, owing to continued industrialization of DNA synthesis, discovery and development of molecular tools and organisms, and increasingly sophisticated modeling and analytic tools. However, we have yet to understand the full potential of engineering biology because of our inability to write and test whole genomes, which we call synthetic genomics. Substantial improvements are needed to reduce the cost and increase the speed and reliability of genetic tools. Here, we identify emerging technologies and improvements to existing methods that will be needed in four major areas to advance synthetic genomics within the next 10 years: genome design, DNA synthesis, genome editing, and chromosome construction (see table). Similar to other large-scale projects for responsible advancement of innovative technologies, such as the Human Genome Project, an international, cross-disciplinary effort consisting of public and private entities will likely yield maximal return on investment and open new avenues of research and biotechnology.